IBD 5 Outcome of perianal fistulae in children with crohn's disease in a tertiary referral centre of inflammatory bowel disease in the United Kingdom. (12th September 2022) - Said, Ghada; Loganathan, Sabarinathan; Kirkham, Sian; Papadopoulos, Michalis; Devadason, David
Abstract : Background: Crohn's disease (CD) is a chronic inflammatory bowel disease that may affect any part of the gastrointestinal tract. Perianal CD disease may include skin tags, fissures, abscesses, strictures, or fistulae. Perianal CD is associated with increased morbidity and poor quality of life. 1 It requires robust medical and surgical treatment. Anti-tumour necrosis factor (TNF) e.g., Infliximab and Adalimumab are the treatment of choice in perianal CD. 2 There is very limited data in the literature about the outcome of perianal and particularly, fistulating CD in children. 3 Magnetic resonance imaging (MRI) pelvis was found to be superior to other imaging modalities in detecting perianal fistulae and abscesses and in delineating the pelvic anatomy and the relationship of the fistula to the anal sphincters. 4 Aim: The aim of the study was to determine the outcome of perianal fistulae in paediatric patients diagnosed with Crohn's disease in a large cohort of patients in a referral centre of paediatric inflammatory bowel disease. Methods: Patients were recruited from IBD clinic in a tertiary referral centre who are diagnosed with Crohn's disease and had a pelvis MRI scan done in the last ten years between 2011–2021. Data was collected retrospectively. Complex perianal fistula was identified as a fistula originating from a high position, associated with a perianal abscess, anorectal stricture, or rectovaginal fistula. 1 Results: Twenty-nine patients were identified who had MRI pelvis scans over a period of 10 years. MRI scan was positive for perianal fistula in 18 patients (62%). Examination under anaesthesia (EUA) was carried out by the paediatric surgical team for 10 patients within an average duration of 1month from doing the MRI scan. Perianal fistula was detected in 50% of EUAs. Ten patients had complex perianal fistulae. Fistulae were present at the time of diagnosis of Crohn's disease in 7 patients. Four patients were on Infliximab at time of detection of fistulae. Biologics were started within an average of three months from the diagnosis of fistulae. Follow up MRI scans were done in eleven patients (61%). Resolution of fistulae was seen in 2 patients (11%), both were on biologics before diagnosis of fistula. Fistulae were not detected in EUA in both patients and one of them had a complex fistula. Conclusion: In our cohort, closure of perianal fistulae in follow up MRI scans was rare despite the use of anti- TNFs.